Structure Control of Iron Ore Education on Sebuku Island - Jamal Rauf Husain; Normansyah Normansyah; Hasbi Bakri (CV Insight Publisher, 2022)
Sebuku is occupied by serpentinized ultramafic (peridotite) rocks, gabbro, and chert which are ophiolite series formed in the oceanic crust, in the middle occupied by tuff and claystones. The purpose of this study was to determine the distribution pattern of iron ore deposits. The research area illustrates that the distribution of Fe elements with high levels of >48% is concentrated in the northeast-southwest part, while Fe elements with levels of <48% are concentrated in the southwest-northwest part of the west. Based on the topographic classification of the research area. The pattern of mineralization follows the structural pattern that occurs, where the lateralization of the source rock is intensive in the crushing zone around the structure that forms the main structure and minor structure. This destruction zone serves as an effective water infiltration medium to accelerate the washing process which forms supergene enrichment zones. The pattern of distribution of mineralization is relatively Northeast-Southwest which in some places is characterized by the straightness of the ridge or morphology with more contrasting and prominent zones on the lidar mosaic map.